Report of the Study Team on Tribal Development Programmes Kerala - Planning Commission (Planning Commission, 1966)
At the instance of the planning Commission the Committee on plan projects constituted in its Resolution No. COPP/Adm/16(l)/66 dated 26th October, 1966, (Annexure I) a Study Team on Tribal Development programmes with the object of giving practical effect to the recommendations made in the Original Fourth Five Year plan Draft Outline for the welfare of scheduled Tribes and for assisting state Governments in evolving concrete schemes of development specially adapted to the needs and conditions of tribal communities and areas.
Committee on Plan Projects Planning Commission
Committee on Plan Projects Planning Commission